2021
DOI: 10.1007/s00246-021-02738-3
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Findings and Correlation with Laboratory Values in Multisystem Inflammatory Syndrome in Children (MIS-C) Associated with COVID-19

Abstract: Cardiac involvement is a common and serious problem in multisystem inflammatory syndrome in children (MIS-C). Echocardiographic evaluation of systolic and diastolic function by traditional, tissue Doppler and three-dimensional (3D) echocardiography was performed in consecutive 50 MIS-C patients during hospitalization and age-matched 40 healthy controls. On the day of worst left ventricular (LV) systolic function (echo-1), all left and right ventricular systolic function parameters were significantly lower ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
2
22
2
2
Order By: Relevance
“…In previous studies, pericardial effusion has been shown in 9–72% of MIS-C patients [ 19 , 35 , 36 ]. Valverde et al [ 19 ] reported 80 (27.9%) patients with pericardial effusion at admission, 66 (25%) of them being mild, 8 (3%) of them moderate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, pericardial effusion has been shown in 9–72% of MIS-C patients [ 19 , 35 , 36 ]. Valverde et al [ 19 ] reported 80 (27.9%) patients with pericardial effusion at admission, 66 (25%) of them being mild, 8 (3%) of them moderate.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study determined 50% mitral regurgitation and 72% pericardial effusion via echocardiography among MIS-C patients on admission, while only 20% had small pericardial effusion and 18% had mild mitral regurgitation at discharge [ 36 ]. Valverde et al [ 19 ] reported the rate of mitral regurgitation and tricuspid regurgitation in a large European MIS-C cohort as 42.5% and 5.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 , 68 The incidence of coronary artery dilation and aneurysms (CAA) in MIS-C is four to twenty four percent. 60 , 61 , 72 , 73 , 74 In patients with KD, the risk of coronary artery thrombosis is directly related to size of CAA and increases exponentially above a z-score of 10. 75 , 76 Depressed left ventricular function (LV) has been noted in a third of patients.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Furthermore, some parameters, such as osteopontin and endothelial glycocalyx degradation, have been suggested as biomarkers for distinguishing severe COVID-19 and MIS-C patients from mild/asymptomatic children with COVID-19 [ 15 , 16 ]. Kavurt et al [ 17 ] evaluated the correlation between cardiac involvement and laboratory parameters and found that LV systolic dysfunction was associated with increased levels of troponin-I, NT-pro BNP, procalcitonin, and ferritin. Chang et al [ 18 ] reported a correlation between impaired global longitudinal strain values and increased levels of IL-6 and IL-8.…”
Section: Discussionmentioning
confidence: 99%